Farmer participation in cooperatives enhances productive services in village collectives: a subjective evaluation approach - Zhang, Yi Zhi; Mi, Yun Sheng; Liu, Chang Jin (Frontiers in Sustainable Food Systems, 2024)
Introduction Provision of agricultural productive services to farmers is crucial for integrating them into the modern agricultural system. However, small-scale farmers often face difficulties in accessing these services. One internationally recognized approach to addressing this issue is the government-led provision of productive services to small-scale farmers. In China, production services are provided through village collectives, which are economic organizations established in townships and villages to manage collective assets, develop resources and economy, and provide services to members. Farmer participation in these services can enhance inclusive service dynamics, improving access to services and promoting rural equity. Methods Farmers’ subjective evaluations directly reflect their access to collective agricultural productive services. This study utilized a binary logit model to analyze the impact and mechanism of farmer participation in cooperatives on the collective supply of agricultural productive services. The study involved 3,900 farmers from 29 provinces (autonomous regions and municipalities) in China. Results and discussion This study proposes for the first time a “cooperative+collective” model for the provision of productive services. In China, safeguarding social equity is one of the important objectives of the Government, and safeguarding and supporting the interests of small-scale farmers is crucial to safeguarding social equity. Participation in cooperatives increased farmers’ access to agricultural productive services. The analysis revealed that farmers have significantly increased their level of access to agricultural production services through participation in the “cooperative+collective” model of productive services. Farmers have participation in cooperatives helped integrate and expand farmers’ demand, leading to the continuous operation and expansion of business scale, thereby enhancing the collective supply of agricultural productive services. Furthermore, those income low-income, older farmers derived more benefits from participating in cooperatives in terms of accessing these services. This study offers empirical evidence supporting the effectiveness of collective agricultural services.